2012
DOI: 10.5144/0256-4947.2012.349
|View full text |Cite
|
Sign up to set email alerts
|

Association of interleukin 4 (-590 T/C) and interleukin 4 receptor (Q551R A/G) gene polymorphisms with acne vulgaris

Abstract: BACKGROUND AND OBJECTIVES Acne vulgaris is a common skin disorder. The complete etiology of this disease remains to be identified; however, it seems that aberrant expression of cytokine genes might be a contributing factor. This study aimed to investigate the association of genetic polymorphisms related to interleukin 4 (IL-4) promotor and receptor (IL-4R) genes as inflammatory modulators with acne vulgaris. DESIGN AND SETTING A case-control study 95 acne patients recru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…In contrast, IL1B − 511 C/T, IL4 − 590 T/C, IL10 − 1082 A/G SNPs and IL1RN variable number tandem repeats (VNTR) all showed no significant association with acne and/or acne severity in the studied populations [ 21 24 ]. Furthermore, a study in Saudi Arabia found that the IL4R Q551R SNP was significantly associated with acne but not acne severity [ 23 ].…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, IL1B − 511 C/T, IL4 − 590 T/C, IL10 − 1082 A/G SNPs and IL1RN variable number tandem repeats (VNTR) all showed no significant association with acne and/or acne severity in the studied populations [ 21 24 ]. Furthermore, a study in Saudi Arabia found that the IL4R Q551R SNP was significantly associated with acne but not acne severity [ 23 ].…”
Section: Resultsmentioning
confidence: 99%
“…IL-4 is involved in the production of IL-17 in CIA. 27 It was reported that common variants of the IL-4/IL-13 pathway do not significantly contribute to RA susceptibility and radiological severity. 28 The levels of IL-4 in the serum and bronchoalveolar lavage fluid of RA patients with interstitial lung disease (ILD) were increased compared with RA patients without ILD.…”
Section: Rheumatoid Arthritismentioning
confidence: 99%
“…The inhibition of IL‐17 may reduce the expression of IL‐1β and IL‐6, which will lead to the deterioration of arthritis. IL‐4 is involved in the production of IL‐17 in CIA . It was reported that common variants of the IL‐4/IL‐13 pathway do not significantly contribute to RA susceptibility and radiological severity .…”
Section: Rheumatoid Arthritismentioning
confidence: 99%
“…In agreement, many studies have found a significant relation between acne prevalence and family history . Several genes had been studied and suggested some evidence that acne is a genetically determined disease and could be inherited …”
Section: Discussionmentioning
confidence: 56%
“…[13][14][15] Several genes had been studied [16][17][18][19] and suggested some evidence that acne is a genetically determined disease and could be inherited. 20 Genetic variations within the VDR gene may cause significant VDR dysfunction. Polymorphisms within VDR gene have been suggested to have a role in skin diseases' pathogenesis through their effect on keratinocytes proliferation and differentiation.…”
Section: Discussionmentioning
confidence: 99%